Peningkatan Keaktifan Belajar Siswa Melalui Layanan Bimbingan Klasikal Berbasis Game Based Learning Pada Siswa Kelas 7B SMP Negeri 4 Madiun - Maghfira Ratu Paramiswari; Tyas Martika Anggriana; Prasetyo (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to describe efforts to improve students’ learning activeness through classical guidance services based on Game Based Learning for Grade 7B students at SMP Negeri 4 Madiun. The research employed a qualitative descriptive approach involving Grade 7B students, the school counselor, and subject teachers as supporting informants. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The findings revealed that the implementation of Game Based Learning in classical guidance services created a more engaging, interactive, and enjoyable learning environment. Students demonstrated increased learning activeness, which was reflected in their improved attention to the material, active participation during guidance activities, willingness to ask questions and express opinions, ability to collaborate with peers, and involvement in drawing conclusions from the learning process. The integration of game elements also enhanced students’ enthusiasm and motivation to participate in classical guidance sessions. These findings indicate that Game Based Learning-based classical guidance services can serve as an effective alternative strategy for enhancing students’ learning activeness. Therefore, school counselors are encouraged to develop innovative and student-centered guidance services to create meaningful learning experiences and support students’ academic and personal development more effectively.